Evaluation of the Tindouf Basin region in Southern Morocco as an analog site for soil geochemistry on Noachian Mars - Oberlin, Elizabeth A; Claire, Mark W; Kounaves, Sam (Astrobiology, 2019)
Locations on Earth that provide insights into processes that may be occurring or may have occurred throughout martian history are often broadly deemed ‘‘Mars analogue environments.’’ As no single locale can precisely represent a past or present martian environment, it is important to focus on characterization of terrestrial processes that produce analogous features to those observed in specific regions of Mars or, if possible, specific time periods during martian history. Here, we report on the preservation of ionic species in soil samples collected from the Tindouf region of Morocco and compare them with the McMurdo Dry Valleys of Antarctica, the Atacama Desert in Chile, the martian meteorite EETA79001, and the in situ Mars analyses from the Phoenix Wet Chemistry Laboratory (WCL). The Moroccan samples show the greatest similarity with those from Victoria Valley, Beacon Valley, and the Atacama, while being consistently depleted compared to University Valley and enriched compared to Taylor Valley. The NO3/Cl ratios are most similar to Victoria Valley and Atacama, while the SO4/Cl ratios are similar to those from Beacon Valley, Victoria Valley, and the Atacama. While perchlorate concentrations in the Moroccan samples are typically lower than those found in samples of other analogue sites, conditions in the region are sufficiently arid to retain oxychlorines at detectable levels. Our results suggest that the Tindouf Basin in Morocco can serve as a suitable analogue for the soil geochemistry and subsequent aridification of the Noachian epoch on Mars. Peer reviewed